2007
DOI: 10.1080/15563650701285412
|View full text |Cite
|
Sign up to set email alerts
|

Insulin versus vasopressin and epinephrine to treat β-blocker toxicity

Abstract: In this swine model, IN/G is superior to V/E to treat beta-blocker toxicity. IN/G has marked inotropic properties while the vasopressor effects of V/E depress CO and contribute to death. Increasing SVR in this condition is detrimental to survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 17 publications
1
55
0
1
Order By: Relevance
“…Current recommendations for the treatment of β-blocker poisoning advocate infusion of catecholamines [12], calcium chloride [13], glucagon [14,15] and extracorporeal life support [16] in instances of refractory cardiovascular collapse. More recently, high-dose insulin-glucose euglycaemia [17,18] and Levosimendan [19] have been demonstrated effective in animal models and clinical cases of β-blocker toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Current recommendations for the treatment of β-blocker poisoning advocate infusion of catecholamines [12], calcium chloride [13], glucagon [14,15] and extracorporeal life support [16] in instances of refractory cardiovascular collapse. More recently, high-dose insulin-glucose euglycaemia [17,18] and Levosimendan [19] have been demonstrated effective in animal models and clinical cases of β-blocker toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Therapieerfolge sind beim Einsatz von Glucagon (50-150 μg/kgKG, [357][358][359][360][361][362][363][364][365][366][367][368][369][370]), hochdosierter Insulin-und Glukosegabe [371][372][373], Lipidemulsionen [374][375][376][377], Phosphodiesterasehemmern [378,379], extrakorporaler Unterstützung und IAPB-Einsatz (intraaortale Ballonpumpe, [380][381][382] …”
Section: Beta-blockerunclassified
“…The dose response relationship of high dose insulin and hemodynamic effects was shown in pigs after induced poisoning with propranolol, where the cardiac output continued to rise in response to insulin doses exceeding 5 Units/kg/hour [13,14]. The inotropic effect of high-dose insulin after verapamil intoxication in canine models has been shown in several studies, even when standard therapy proved ineffective [15][16][17][18].…”
Section: Introductionmentioning
confidence: 92%
“…The inotropic effect of high-dose insulin after verapamil intoxication in canine models has been shown in several studies, even when standard therapy proved ineffective [15][16][17][18]. In short, animal studies showed the ability of high dose insulin to reverse catecholamine and glucagon-refractory overdoses with beta-adrenergic blockers and/or calcium channel blockers, as well as partial reversal of LPS induced shock [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%